Deformation Characterisation and Distress Diagnosis of a Metro Shield Tunnel by Adjacent Constructions - Ting-jin Liu; Si-wei Chen; Hong-yuan Liu (Advances in Civil Engineering)
This paper presents a case history of the developmental effect of a large-area excavation, 8 high-rise main buildings, a series of annex constructions, and ground overloaded building demolition on the deformation characteristics of an existing shield tunnel within Guangzhou Metro Line No. 1 in close proximity to the development. The shield tunnel lies in a sandy layer of the typical upper-soft and lower-hard strata in Guangzhou district, and the deformation of the tunnel has been monitored since the tunnel was put into operation. The monitoring results reveal that the adjacent construction induces an excessive tunnel settlement with a maximum of 14.4 mm and an excess tunnel displacement with a maximum of 5.2 mm, which are within the corresponding limitations of the codes for the safe operation of urban rail transit tunnels. While the station expansion project is being conducted beside the tunnels, a series of tunnel distresses, including large-area water seepage, spalling concrete blocks, and segmental cracks, are recorded. Our field monitoring data indicate that the tunnel is subjected to further vertical contraction and horizontal expansion due to the station expansion project, and a maximum tunnel flattening rate of 36.78% is detected. Furthermore, the tunnel linings are studied numerically and theoretically to obtain the limitations of tunnel deformation and discuss why tunnel distresses of water seepage, concrete spalling, and segmental cracking occur. Finally, on the basis of the analyses and discussions above, counteracting corrective measures, including compensation grouting soil strengthening and bonded steel plates, are adopted as exterior and interior strengthening methods, respectively, to eliminate further tunnel distresses and ensure safe operation. The lessons learned and summarized in this study may help prevent similar tunnel distresses from reoccurring in the future.